PLURALISME HUKUM PROGRESIF: MEMBERI RUANG KEADILAN BAGI YANG LIYAN - Eko Mukminto; Awaludin Marwan (Faculty of Law, Universitas Diponegoro, 2019)
When ideological contestation in law is controlled by the logic of the majority. Then the consequences of the legal logic will be controlled by the logic of oppression. In this context, minorities whether based on religion, ethnicity, gender or sexuality are difficult to pursuit justice. Access to justice is possible as long as minority representation is also present in state law. This paper aims to examine the concept of legal pluralism in Progressive law. Thus, it will also provide alternative ideas for resolving the problem of discrimination of minority groups. Satjipto Rahardjo’s Progressive law has a philosophical basis that sees that the discourse of law is never be final and legal pluralism will provide justice. In the progressive law reasoning, legal pluralism will be discussed with recognition and redistribution political theory, so that it will tear down constellation of hierarchical structures and provides justice for minorities or “the others”. Therefore, state law is no longer the rule of majority.